Tangerang Regency Government Policy in Addressing School Dropouts - Farchan Nurhakim; Wasehudin; Encep Syarifudin; Agus Gunawan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This article discusses the extent of the causes and efforts that the government can take to overcome school dropout in Tangerang Regency. The type of research used in this research is qualitative narrative. The results of the research will be in the form of data excerpts from the origins of interviews, photos, field notes, personal documents, voice recordings and other documents. This research wants to discuss (1) The causes of children dropping out of school, namely: the economic situation of the family, the educational background of the father and mother, the status of the father in society as well as employment and social psychological correlation between parents and between children and parents, (2) Policy Analysis Regional government in overcoming school dropouts in: (a) Optimizing the distribution of scholarships through BOS funds, KIP, family hope events, and/or similar assistance, (b) Regional government and school principals encourage the community, public figures, DUDI, to encourage completion of education according to the level, (c) Counseling and guidance for children's parents by the Education Department, (d) Strengthening family education.